2010
DOI: 10.1029/2009jd012626
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mass, hygroscopic growth, and droplet activation of coated soot particles during LACIS Experiment in November (LExNo)

Abstract: The LACIS Experiment in November (LExNo) campaign was conducted in November 2005 at the Atmospheric Composition Change the European Network of Excellence (ACCENT) site Leipzig Aerosol Cloud Interaction Simulator (LACIS). The goal of LExNo was to provide deeper insight into the activation properties of coated soot particles imitating aged combustion aerosol particles. The aerosols were prepared by starting with spark‐generated soot particles. In some experiments the soot particles were compacted by exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…No (complete) activation was found for soot from aviation fuel, wood and crude oil. Henning et al (2010) observed, that coated spark soot acts as CCN (d p,0 = 85 nm activated between 0.3 and 0.6 %). Zhang et al (2008) investigated the activation of sulfuric acid coated flame soot at two supersaturations (0.2 and 0.4 %), but they found no activation for the uncoated soot at the same supersaturations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No (complete) activation was found for soot from aviation fuel, wood and crude oil. Henning et al (2010) observed, that coated spark soot acts as CCN (d p,0 = 85 nm activated between 0.3 and 0.6 %). Zhang et al (2008) investigated the activation of sulfuric acid coated flame soot at two supersaturations (0.2 and 0.4 %), but they found no activation for the uncoated soot at the same supersaturations.…”
Section: Introductionmentioning
confidence: 99%
“…The GF increased with increasing sulfur content of the fuel. Weingartner et al (1997) and Henning et al (2010) used the same type of spark generator with nitrogen as carrier gas as was used in this study. They observed no hygroscopic growth for the uncoated spark soot, but after coating with soluble substances a hygroscopic growth occurred .…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of these issues, particularly the need for large scale coverage with its implied mandate for remote retrieval of aerosol properties that can predict CDNC, numerous studies have explored possible simplifications to the aerosol-CDNC relationship, for example using such parameters as size dependent hygroscopicity (e.g., Petters and Kreidenweiss, 2008;Henning et al, 2010). A particularly simplified relationship has been suggested by the study of Dusek et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The extended classic Köhler theory has been applied for most of the studies to include the insolubility of BC inclusion (i.e. Weingatner et al, 1997;Zhang et al, 2008;Henning et al, 2010), which has mostly explained the increased hygroscopicity of soot particles by attributing the hygroscopicity from each of the components present.…”
Section: Introductionmentioning
confidence: 99%